MAQASHID ASY-SYARI’AH DALAM MANAJEMEN BISNIS ISLAM - Andi Yuni Dharmawati Tahang; Pardiman Pardiman; Ridwan Basalamah (Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
This article aims to analyze Maqasid as-Syaria in Islamic business management. This research is a qualitative research of the library. The study results stated that business activities require good governance, so the business can continue to develop and advance. In addition, Muslims must base business management on the provisions of Shari'a. The practicality of Islamic business management is in line with Maqasid as-Syaria. Where it has fulfilled the element of benefit based on hifdzu ad-dien, hifdzu annafs, hifdzu al-aql, hifdzu an-nasl, and hifdzu al-maal.